1983
DOI: 10.1002/j.1460-2075.1983.tb01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodulin-35: a subunit of specific uricase (uricase II) induced and localized in the uninfected cells of soybean nodules

Abstract: Nodulin‐35, a protein specific to soybean root nodules, was purified under non‐denaturing conditions (DEAE‐cellulose followed by Sephacryl S‐200 chromatography) to homogeneity. The holoprotein showed uricase (EC 1.7.3.3) activity. Analytical ultracentrifugation under non‐denaturing conditions revealed a molecule of 124 kd, S°20W = 8.1; however, under denaturing conditions a value of 33 kd, S°20W = 1.9, was obtained. This indicated that nodulin‐35 is the 33‐kd subunit of a specific soybean root nodule uricase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
2

Year Published

1985
1985
1992
1992

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 26 publications
8
90
2
Order By: Relevance
“…Uricase and to some extent xanthine dehydrogenase could be regarded as nodule-specific. The 33-kD subunit of uricase has been demonstrated to be identical to the nodule-specific nodulin 35 (3,15). On the basis of immunological studies, xanthine dehydrogenase from soybean has been suggested by Nguyen et al (20) to be nodule-specific, while Triplett et al (29) found significant cross-reactivity in roots, stems, and leaves using monoclonal antibodies raised against soybean nodule xanthine dehydrogenase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uricase and to some extent xanthine dehydrogenase could be regarded as nodule-specific. The 33-kD subunit of uricase has been demonstrated to be identical to the nodule-specific nodulin 35 (3,15). On the basis of immunological studies, xanthine dehydrogenase from soybean has been suggested by Nguyen et al (20) to be nodule-specific, while Triplett et al (29) found significant cross-reactivity in roots, stems, and leaves using monoclonal antibodies raised against soybean nodule xanthine dehydrogenase.…”
mentioning
confidence: 99%
“…One of the above enzymes, uricase, has been shown to be nodule-specific (3) and has been grouped as a class II nodulin.…”
mentioning
confidence: 99%
“…On the other hand, uricase II and other enzymes of ureide metabolism have been detected in uninfected cells of soybean nodules (4). Specifically, uricase II has been localized within the peroxisomes of these cells (2,22). The enzyme uricase (Urate oxidase, EC 1.7.3.3.)…”
mentioning
confidence: 99%
“…Also, the possible existence of apoferritin in normal Bradyrhizobium nodules may be subsequently elucidated. This latter aspect is particularly interesting because nodulin-35 (uricase II) is induced very early in nodule development, but significant uricase II activity is not detected until the commencement of nitrogen fixation (6). Thus, the 600 kD apoferritin, like nodulin-35, may undergo some modifications before it is activated to take up iron.…”
Section: Effects Of Bradyrhizobial/rhizobial Strains On the Presence Ofmentioning
confidence: 99%